Estimated need for surgery worldwide based on prevalence of diseases: a modelling strategy for the WHO Global Health Estimate - John Rose, MD; Thomas G Weiser, MD; Phil Hider, FAFPHM; Leona Wilson, FANZCA; Prof. Russell L Gruen, PhD; Prof. Stephen W Bickler, MD (Elsevier, 2015)
Background: Surgery is a foundational component of health-care systems. However, previous efforts to integrate surgical services into global health initiatives do not reflect the scope of surgical need and many health systems do not provide essential interventions. We estimate the minimum global volume of surgical need to address prevalent diseases in 21 epidemiological regions from the Global Burden of Disease Study 2010 (GBD). Methods: Prevalence data were obtained from GBD 2010 and organised into 119 disease states according to the WHO's Global Health Estimate (GHE). These data, representing 187 countries, were then apportioned into the 21 GBD epidemiological regions. Using previously defined values for the incident need for surgery for each of the 119 GHE disease states, we calculate minimum global need for surgery based on the prevalence of each condition in each region. Findings: We estimate that at least 321·5 million surgical procedures would be needed to address the burden of disease for a global population of 6·9 billion in 2010. Minimum rates of surgical need vary across regions, ranging from 3383 operations per 100 000 in central Latin America to 6495 operations per 100 000 in western sub-Saharan Africa. Global surgical need also varied across subcategories of disease, ranging from 131 412 procedures for nutritional deficiencies to 45·8 million procedures for unintentional injuries. Interpretation: The estimated need for surgical procedures worldwide is large and addresses a broad spectrum of disease states. Surgical need varies between regions of the world according to disease prevalence and many countries do not meet the basic needs of their populations. These estimates could be useful for policy makers, funders, and ministries of health as they consider how to incorporate surgical capacity into health systems. Funding: US National Institutes of Health.